Andrographolide derivative as antagonist of vitamin D receptor to induce lipidation of microtubule associate protein 1 light chain 3 (LC3). (1st December 2021) - Ding, Mo-Yu; Peng, Yuran; Li, Feng; Li, Zheng-Qing; Wang, Decai; Zhou, Guo-Chun; Wang, Ying
Graphical abstract: Abstract: Lipidation of microtubule associated protein 1 light chain 3 (LC3) is the critical step in autophagosome formation, numerous efforts have been made to design and develop small molecules that trigger LC3 lipidation to activate autophagy. In this study, we discovered a series of andrographolide derivatives as potent antagonists of vitamin D receptor (VDR) by luciferase reporter assay. Structure-activity-relationship study revealed that andrographolide derivative ZAV-12 specifically inhibited VDR signaling but not NF-κB or STAT3 activation. Western blot analysis indicates that ZAV-12 markedly triggered lipidation of LC3 in MPP + -induced Parkinsonism in vitro in an mTOR-independent manner. The ZAV-12 triggered lipidation was mediated through SREBP2 activation instead of changing expression levels of lipid synthesis genes. Furthermore, ZAV-12 treatment increased the ratio of LC3-II/LC3-I and oligomerization of A53T α-synuclein (SNCA) in SNCA triggered neurotoxicity. Taken together, these results demonstrate the therapeutic potential of VDR antagonist as novel drug candidate for neurodegenerative diseases.